Association between COVID-19 severity with liver abnormalities: A retrospective study in a referral hospital in Indonesia - Maimunah, Ummi; Kholili, Ulfa; Vidyani, Amie; Sugihartono, Titong; Tanaya, Willa M.; Wessels, Firda I.; Alshawsh, Mohammed A.; Miftahussurur, Muhammad (Narra Sains Indonesia, 2024)
Coronavirus disease 2019 (COVID-19) is characterized by an acute respiratory infection with multisystem involvement and the association of its severity to liver function abnormalities is not well characterized. The aim of this study was to assess the association between the severity of COVID-19 patients and liver function abnormalities. This retrospective study included adult patients with confirmed COVID-19, which were classified as non-severe or severe according to World Health Organization guidelines. Liver function test results were compared between the severity groups. A total of 339 patients were included of which 150 (44.25%) were severe cases. The male-to-female ratio was 0.9:1 and 3:2 in the non-severe and severe groups, respectively (p=0.031). Aspartate aminotransferase (AST), alanine transaminase (ALT), and total bilirubin levels and acute liver injury (ALI) incidence were significantly higher in the severe group compared to non-severe group (p<0.001, p<0.001, p=0.025, p=0.014, respectively). In contrast, albumin levels were significantly lower (p=0.001). Multivariate analysis showed that ALI was significantly associated with human immunodeficiency virus (HIV) infection (odds ratio (OR): 5.275; 95% confidence interval (CI): 1.165–23.890, p=0.031), hemoglobin level (OR: 1.214; 95%CI: 1.083–1.361, p=0.001), and hypoalbuminemia (OR: 2.627; 95%CI: 1.283–5.379, p=0.008). Pre-existing liver diseases were present in 6.5% of patients. No significant differences were observed between the groups based on COVID-19 severity and ALI presence. Liver function test abnormalities, including ALI, are more prevalent in patients with severe COVID-19 infection. HIV infection, high hemoglobin levels, and hypoalbuminemia may be potential risk factors for ALI.